New species of mammaliaform and the cranium of Borealestes (Mammaliformes: Docodonta) from the Middle Jurassic of the British Isles - Panciroli, E; Benson, R; Fernandez, V; Butler, RJ; Fraser, NC; Luo, Z-X; Walsh, S (Oxford University Press, 2021)
Docodonta are one of the earliest diverging groups of mammaliaforms, and their morphology provides key information on the transition between non-mammalian cynodonts and Mammalia. We describe the partial skulls of two docodontans Borealestes serendipitus and Borealestes cuillinensis sp. nov. from the Kilmaluag Formation (Middle Jurassic: Bathonian), Isle of Skye, Scotland. We visualize their cranial anatomy using laboratory and synchrotron X-ray micro-CT. The skulls belong to two partial skeletons, currently comprising the most complete Mesozoic mammal fossils reported from the British Isles. The associated upper and lower dentitions show that the lower dentition of Borealestes is not diagnostic to species level. We establish, B. cuillinensis, based on upper molar characters, and re-identify upper molars previously assigned to ‘Borealestes’ mussettae as belonging to B. cuillinensis. ‘Borealestes’ mussettae, based on distinctive lower molars, is found to be morphologically and phylogenetically distinct from Borealestes, necessitating assignment to a new genus, Dobunnodon gen. nov. The skulls of Borealestes retain many plesiomorphic features seen in Morganucodon but absent in more crownward mammaliaforms. Our study highlights that generic and species taxonomy of docodontans are more reliable when based on both upper and lower teeth, while lower molar morphology may underrepresent the true diversity of Mesozoic mammaliaforms.